2018
DOI: 10.20950/1678-2305.2018.288
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de espécies de peixes não nativos em um rio Neotropical sob a influência da atividade aquí­­cola

Abstract: The introduction of non-native species is one of the greatest global changes and is a substantial threat to continental fish fauna. This study aimed to evaluate the composition and structure of the fish assemblage of the Azul River, a tributary along the left margin of the Piquiri River basin, to determine the occurrence, abundance and spatial distribution of non-native fish species. Sampling was carried out from February to November 2014 at three sites along the river using of electric fishing equipment. Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(68 reference statements)
1
0
0
Order By: Relevance
“…The putative effect of anthropogenic activities on fish eDNA recovery herein described corroborates the well-known impacts of human actions (e.g. construction of dams, species introduction, pollution) leading to biotic homogenization (Agostinho et al, 2008, Ribeiro et al, 2017.…”
Section: Anthropogenic Impacts and Species Richnesssupporting
confidence: 82%
“…The putative effect of anthropogenic activities on fish eDNA recovery herein described corroborates the well-known impacts of human actions (e.g. construction of dams, species introduction, pollution) leading to biotic homogenization (Agostinho et al, 2008, Ribeiro et al, 2017.…”
Section: Anthropogenic Impacts and Species Richnesssupporting
confidence: 82%
“…The high abundance of O. niloticus and occurrence of C. rendalli found in the streams evaluated are due to escapes from ponds used for aquaculture activities, denoting the need for efficient escape containment mechanisms (Nobile et al 2019). The occurrence of non-native species due to aquaculture activities is also reported by others studies on the region and can be attributed to the low distances between fish ponds and streams, which allows escapes through effluent waters under inadequate management, rupture or overflow in rainy periods, and intentional releases (Orsi & Agostinho 1999, Forneck et al 2016, Ribeiro et al 2018, Casimiro et al 2018, Forneck et al 2020.…”
Section: Discussionsupporting
confidence: 57%
“…Margalef (1995) reported that tidal containment systems have low richness (<5 bits ind -1 ); and it was observed that the tidal containment structures of both areas might also be related to the low richness. This type of system prevents migratory movements, causing changes in the abundance, distribution, and even in the genetic structure of ichthyofauna (Agostinho et al, 2008;Oliveira and 2010).…”
Section: Discussionmentioning
confidence: 99%